Науково-видавнича діяльність Національної академії наук України - Діденко, Ю.В.; Радченко, A.І. (Наука та наукознавство, 2018)
Висвітлено основні напрями науково-видавничої діяльності Національної академії наук України від її заснування до сьогодні. Коротко окреслено історію науково-видавничої справи і Редакційно-видавничої ради (нині Науково-видавнича рада НАН України). Наведено засадничі принципи, завдання та форми роботи Науково-видавничої ради НАН України на сучасному етапі — після здобуття Україною незалежності. Матеріал присвячено 100-річному ювілею вітчизняної Академії наук. Отражены основные направления научной и издательской деятельности Национальной академии наук Украины от ее основания до наших дней. Коротко очерчена история научно-издательского дела и Редакционно-издательского совета (в настоящее время Научно-издательский совет НАН Украины). Более подробно описана работа академического издательства «Наукова думка», получившего мировое признание во второй половине ХХ века. Наиболее подробные данные касаются нового этапа академической издательской деятельности в Украине начиная с 1992 года — после обретения Украиной независимости. Main areas of the scientific and publishing activity of the National Academy of Sciences of Ukraine from the time of its foundation are revealed. A short review of the history of the Scientific Publishing and Editing and Publishing Council (now — the Scientific Publishing Council of the National Academy of Sciences of Ukraine) is given. A more detailed description is about the operation of the Academy’s Publishing House “Naukova Dumka”, which gained global recognition in the second half of 20 century. The most detailed data concerns the new phase of academic printing and publishing in Ukraine, beginning with 1992, after Ukraine gained independence.